An improvement to integrated model of electro pneumatic circuit for material handling in a manufacturing cell - Mansor, Mohamad Norani (2005)
Pneumatic circuit are very widely used in automating plants especially manufacturing plants. These circuits are implemented for material handling, process control and general automation. Selecting an effective design, components and appropriate system will be a critical item in installing an effective and efficient system. One sure way of acquiring this is the application of software especially those that have comprehensive analytical capability. In this project the author used Automation Studio to study the effect of adding extra component and valve to a three cylinder integrated material handling system. The evaluation has shown that adding components have shown some positive effect on the system. However some components provide advantages some do not. Automation Studio has prove to be an effective tool to determine this.